(untitled) (Journal of Social Sciences Review, 2023)
Industrial pollution has adverse effects on the human health. The prevalence of several toxic and chemical substances emitted from industries affects human health badly. The present research study has mainly focused on analysing the socio-economic conditions, health issues and causal environmental factors associated with prevalent health problems of the respondents residing near the S.I.T.E area in Karachi. In order to analyse the impact of industrial pollution on human health, the researcher has obtained data from 150 study participants through a structured questionnaire based on five points Likert scale. Two different groups, factory workers and people residing near the industrial area are recruited for the collection of data. A sample size of 75 workers and 75 heads of the house residing within 2 K.M range of industrial area were recruited by using a systematic random sampling technique. The findings of the research study show that there is a significant relationship between air pollution and the prevalence of respiratory diseases. The main pollution sources in the study areas were industries, traffic congestion, and domestic and water pollution. It is suggested that mitigation strategies should be formulated to combat industrial pollution, and significant healthcare services should be provided to the people residing near the industrial areas. Objective: The present research study has mainly focused to assess the socio-economic conditions, health issues and causal environmental factors associated with prevalent health problems of the respondents residing near the S.I.T.E area Karachi. Methodology: In order to assess the impact of industrial pollution on human health the total 150 respondents were recruited for the data collection. Two different groups, factories workers and people residing near the industrial area were selected for the data collection. A sample size of 75 workers and 75 heads of the house residing within 2 K.M range of industrial area were recruited by using systematic random sampling technique. Results: Findings of the research study show that there is a significant relationship between air pollution and prevalence of respiratory diseases. Main pollution sources in the study areas were industries, traffic congestion, domestic and water pollution. The respondents were facing some common, respiratory and serious diseases like Asthma, cardiovascular, high blood pressure, cancer, skin diseases and diarrhea as well. Recommendation: It is suggested that mitigation strategies should be formulated to combat industrial pollution and significant health care services should be provided to these people residing near the industrial areas.